Improving the effectiveness of anticancer properties of capecitabine using aminocaproic acid-hyaluronic acid/sulfonamide IR-MOF nanoplatform for colon cancer treatment - Sedigheh Alavinia; Ramin Ghorbani-Vaghei; Rasool Haddadi; Khashayar Sanemar; Seyed Sepehr Uroomiye; Alireza Nourian (Carbohydrate Polymer Technologies and Applications)
Colorectal cancer (CRC) is one of the most prevalent and deadly malignancies worldwide, accounting for a significant proportion of cancer-related mortality. Despite advancements in treatment modalities, tumor recurrence and the development of metastases remain major challenges in CRC management. Current chemotherapeutic agents, such as capecitabine (CAP), are widely used in CRC treatment. However, their clinical efficacy is often limited by poor bioavailability and systemic toxicity, which can compromise patient outcomes. Therefore, it is important to find novel ways to prevent these limitations. In this study, we developed a novel nanoscale Zn-sulfonamide isoreticular metal-organic framework (Sul-IRMOF) modified with 6-aminocaproic acid-hyaluronic acid (Sul-IRMOF-ACA-HA) to improve drug release behavior. The MTT assay demonstrated that Sul-IRMOF-ACA-HA@CAP exhibited a 3.2-fold increase in cytotoxicity against CT26 colon cancer cells compared to pure CAP (p ≤ 0.05) after 72 h of treatment. Flow cytometry analysis revealed a 1.52-fold increase in apoptosis induction in CT26 cells treated with Sul-IRMOF-ACA-HA@CAP compared to pure CAP. Tumor weight studies showed that Sul-IRMOF-ACA-HA@CAP reduced tumor weight by 80.3 % compared to the control group (p ≤ 0.05), while CAP treatment achieved only a 25.79 % reduction. Histological assay results are consistent with MTT assay and flow cytometry analysis. The formulation also demonstrated a high entrapment efficiency of 97 % and a sustained release profile in a pH-dependent manner. Furthermore, biochemical analysis of tumors revealed a significant reduction in tumor markers (e.g., SOD, GSH, CAT, and total thiol) in the Sul-IRMOF-ACA-HA@CAP group compared to CAP alone (p ≤ 0.05). This formulation combines the unique properties of HA for receptor-mediated targeting, ACA for enhanced stability, and a Sul-IRMOF for controlled release. The significance of this study lies in its potential to overcome the limitations of conventional chemotherapy by providing a smart, targeted, and pH-responsive drug delivery system that enhances therapeutic efficacy and minimizes systemic toxicity. The combination of HA, ACA, and Sul-IRMOF represents a significant advancement in the field of nanotechnology-based cancer therapy. As a result, Sul-IRMOF-ACA-HA has proven to be effective anticancer formulation and overcomes the issues associated with free CAP.